Vane (Szocialista brigàd, Radio Prague, SAK, Savez Sindikata Jugoslavije, ČSD from coll. Hošek, VIJ), cloth (IRA, UTM), pan-holder (BSP) and emblem (FSG, ABVV from coll. ETUC)
Vane (Szocialista brigàd, Radio Prague, SAK, Savez Sindikata Jugoslavije, ČSD from coll. Hošek, VIJ), cloth (IRA, UTM), pan-holder (BSP) and emblem (FSG, ABVV from coll. ETUC).